Foreign Direct Investment Spillovers and Economic Growth: Evidence from Asian Emerging Countries - Lodi Bagus Rismawan; Tri Haryanto; Rossanto Dwi Handoyo (Universitas Muhammadiyah Ponorogo, 2021)
Research on FDI in promoting economic growth has been the focus of recent decades, especially in developing countries. Foreign direct investment can be one of the main objectives in increasing economic growth. FDI is assumed to indirectly contribute to economic growth through a spillover effect on the absorption capacity of a country by increasing the stock of human capital and the quality of institutions. This study aims to analyze the spillover effect of FDI on economic growth in Asian emerging markets. The data were analyzed using dynamic panel regression (GMM) during 2008-2017 period with STATA 14 software.The results in this study strongly indicate that the spillovers of FDI is proven to be able to drive economic growth through human capital and institutions in Asian emerging markets.